Advanced microscopy resolves dynamic localization patterns of stress-induced mitogen-activated protein kinase (SIMK) during alfalfa root hair interactions with Ensifer meliloti - Hlaváčková, Kateřina; Šamajová, Olga; Hrbáčková, Miroslava; Šamaj, Jozef; Ovečka, Miroslav (Journal of experimental botany, 2023)
Leguminous plants have established mutualistic endosymbiotic interactions with nitrogen-fixing rhizobia to secure nitrogen sources in root nodules. Before nodule formation, the development of early symbiotic structures is essential for rhizobia docking, internalization, targeted delivery, and intracellular accommodation. We recently reported that overexpression of stress-induced mitogen-activated protein kinase (SIMK) in alfalfa affects root hair, nodule, and shoot formation, raising the question of how SIMK modulates these processes. In particular, detailed subcellular spatial distribution, activation, and developmental relocation of SIMK during early stages of alfalfa nodulation remain unclear. Here, we characterized SIMK distribution in Ensifer meliloti-infected root hairs using live-cell imaging and immunolocalization, employing alfalfa stable transgenic lines with genetically manipulated SIMK abundance and kinase activity. In the SIMKK-RNAi line, showing down-regulation of SIMKK and SIMK, we found considerably decreased accumulation of phosphorylated SIMK around infection pockets and infection threads. However, this was strongly increased in the GFP-SIMK line, constitutively overexpressing green fluorescent protein (GFP)-tagged SIMK. Thus, genetically manipulated SIMK modulates root hair capacity to form infection pockets and infection threads. Advanced light-sheet fluorescence microscopy on intact plants allowed non-invasive imaging of spatiotemporal interactions between root hairs and symbiotic E. meliloti, while immunofluorescence detection confirmed that SIMK was activated in these locations. Our results shed new light on SIMK spatiotemporal participation in early interactions between alfalfa and E. meliloti, and its internalization into root hairs, showing that local accumulation of active SIMK modulates early nodulation in alfalfa.
Keywords: Alfalfa; Symbiosis; rostliny; infection pocket; infection thread; light-sheet fluorescence microscopy; Plants; subcellular localization; Mitogen-Activated Protein Kinases; Ensifer meliloti; root hairs; Microscopy; immunolocalization; symbióza; mitogenem aktivované proteinkinasy; Sinorhizobium meliloti; SIMK; Medicago sativa; mikroskopie; MAPKs